A competitive analysis of port of Hong Kong: From external to internal - Zihua Liu; Dong Yang; Y. N. Eppie Ng (Journal of Shipping and Trade (JST), 2020)
This paper aims to analyse the competitive equilibrium of Hong Kong international port after the cooperation among terminal operators. To achieve our research objective, a comprehensive analysis framework is proposed. We assume that the port services provided by Shenzhen and Hong Kong have heterogeneity, thus apply Cournot price competition model to understand the external competition. We find that the heterogeneity level can affect the demand of Hong Kong international port. For different heterogeneity levels, different competitive equilibriums among terminal operators of Hong Kong are discussed. We further apply Edgeworth model and Stackelberg Leadership Model to describe the internal competition of Hong Kong international port. Based on analysis, some recommendations are provided to the terminal operators of Hong Kong.
Keywords: 650; Terminal/port competition; Service heterogeneity; Cournot price competition; Edgeworth model; Stackelberg leadership model